(3JdbjM aghe Cgd GdCKQ aj Yjhf GdJGQjN hGdSjQs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3PcQ YOO GdCfHjGA hGdeQSdjf s
(3BNQgG (B:s
(3hGdRgGO GdMSf Hf eSde GdaGQS s
(3GfXQ CjkVG Qbe (B188(3h(B1008 (3JGQjNs
(3HgG JeRjb hWeSs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs